Landslide Susceptibility Zonation Using Analytic Hierarchy Process Method in the Karangbolong Hills Area, Indonesia - Susilowati, Susilowati; Radityo, Daniel; Aminulloh, Dzikru; Rahayu, Ririn Wuri (Journal of Earth and Marine Technology (JEMT), 2025)
The highest frequency of landslides in Kebumen Regency is observed in the Ayah Subdistrict and Buayan Subdistrict, which are in the southern part of the Karangbolong Hills. This area are the targets for the construction of the 14.03 km Ayah-Jladri Southern Cross Road (JJLS). Consequently, the objective of this study is to create a landslide susceptibility map utilizing the Analytic Hierarchy Process (AHP) methodology. Some causative factors are used to develop landslide susceptibility maps i.e. elevation, slope gradient, aspect and curvature, lithology and lineament density, distance from streams, land use and distance from roads. A total number of 128 landslide events are considered in the study. This method identified five susceptibility zones based on LSI value: very low (141.79-241.74), low (241.75-293.73), moderate (293.74-334.52), high (334.53-374.89), and very high (374.90-460.50). The landslide susceptibility map was validated, with an AUC value of 0.749, suggesting that the map provides good results.